2022
DOI: 10.3389/fneur.2022.968037
|View full text |Cite
|
Sign up to set email alerts
|

A visualized nomogram to online predict futile recanalization after endovascular thrombectomy in basilar artery occlusion stroke

Abstract: Background and purposeFutile recanalization occurs in a significant proportion of patients with basilar artery occlusion (BAO) after endovascular thrombectomy (EVT). Therefore, our goal was to develop a visualized nomogram model to early identify patients with BAO who would be at high risk of futile recanalization, more importantly, to aid neurologists in selecting the most appropriate candidates for EVT.MethodsPatients with BAO with EVT and the Thrombolysis in Cerebral Infarction score of ≥2b were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…4 Regarding factors associated with futile recanalization, our study further confirmed that diabetes mellitus, baseline NIHSS score, baseline pc-ASPECTS score, and PC-CS score were predictors of futile recanalization, which is in line with previous studies. 15-19 We also showed that higher NLR values, PTR time, and incomplete reperfusion were associated with futile recanalization. What's more, multiple stent retriever passes were associated with a high proportion of futile recanalization in patients with late time windows.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…4 Regarding factors associated with futile recanalization, our study further confirmed that diabetes mellitus, baseline NIHSS score, baseline pc-ASPECTS score, and PC-CS score were predictors of futile recanalization, which is in line with previous studies. 15-19 We also showed that higher NLR values, PTR time, and incomplete reperfusion were associated with futile recanalization. What's more, multiple stent retriever passes were associated with a high proportion of futile recanalization in patients with late time windows.…”
Section: Discussionmentioning
confidence: 77%
“…[IQR], 63 [54-71] years vs 65 [58-74] years; P = .02), had a higher systolic blood pressure on admission (median[IQR], 146 mm Hg vs 151 [135-169] mm Hg; P = .03), higher neutrophil-to-lymphocyte ratio (NLR) (median [IQR], 6.3 [4.1-10.2] vs 9.2[5.8-13.4]; P < .001), higher baseline NIHSS score (median [IQR], 18[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] vs 30[21][22][23][24][25][26][27][28][29][30][31][32][33][34]; P < .001), lower baseline pc-ASPECTS score (median [IQR], 9[8][9][10] vs 8[6][7][8][9]; P < .001), lower PC-CS score (median [IQR], 5[4][5][6] vs 4 [3-6]; P < .001), and longer puncture to recanalization time (PTR) (median [IQR], 87 [62-128] minutes vs 110 [11-155] minutes; P < .001). In addition, the proportions of patients with diabetes mellitus (87 of 328 patients [26.5%] vs 21 of 194 patients [16.0%]; P = .005), coronary heart disease (59 of 328 patients [18.0%] vs 21 of 194 patients [10.8%]; P = .03), and symptomatic intracranial hemorrhage (24 of 328 patients [7.4%] vs 3 of 194 patients [1.5%]; P = .004) in the futile recanalization group were higher than those in the meaningful recanalization group.…”
mentioning
confidence: 99%
“…Our nomogram incorporated variables, including age, preoperative SBP, OTR, and 24 h ICH, and showed good discriminatory ability, Nomograms are highly reliable and practical estimation tools that help predict prognosis and enhance clinical decisions on personalized treatment by combining different prognostic and determinant data and evaluating them in combination with several powerful event indicators (9)(10)(11). They are also widely used to predict the prognosis of stroke, including FR (6,12). Based on radiomics and with the help of machine learning, Yuqi Luo et al established nomogram to predict FR, focusing on the use of machine learning methods to integrate clinical information and imaging information, which is complex and limits its extensional generalizability (5).…”
Section: Discussionmentioning
confidence: 92%
“…The studies were included if they met the following criteria: (1) Aged ≥18 years old; (2) AIS: within 8 h; (3) baseline admission National Institute of Health Stroke Scale (NIHSS) score ≥ 6;(4) modified Rankin Scale (mRS) score before onset ≤ 2; (5) angiography confirmed intracranial internal carotid artery, middle cerebral artery (MCA) trunk acute obstruction in patients; (6) The subject (or his guardian) agreed to participate in the study and signed an informed consent form.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation